Inflammation, immune activation, and cardiovascular disease in HIV. (19th June 2016) - Nou, Eric; Lo, Janet; Grinspoon, Steven K.
Abstract : Cardiovascular disease is one of the leading causes of morbidity and mortality in people living with HIV. Several epidemiological studies have shown an increased risk of myocardial infarction and stroke compared to uninfected controls. Although traditional risk factors contribute to this increased risk of cardiovascular disease, HIV-specific mechanisms likely also play a role. Systemic inflammation has been linked to cardiovascular disease in several populations suffering from chronic inflammation, including people living with HIV. Although antiretroviral therapy reduces immune activation, levels of inflammatory markers remain elevated compared to uninfected controls. The causes of this sustained immune response are likely multifactorial and incompletely understood. In this review, we summarize the evidence describing the relationship between inflammation and cardiovascular disease and discuss potential anti-inflammatory treatment options for cardiometabolic disease in people living with HIV.